\(\left(x^2-2\right)\left(x^2+x-1\right)-x\left(x^3+x^2-3x-2\right)\)
\(=x^4-2x^2+x^3-2x-x^2+2-x^4-x^3+3x^2+2x\)
\(=\left(x^4-x^4\right)+\left(x^3-x^3\right)+\left(3x^2-2x^2-x^2\right)+\left(2x-2x\right)+2\)
\(=2\)
\(\Rightarrow\) b/t trên ko phụ thuộc vào biến \(\left(đpcm\right)\)
\(\left(x^2-2\right)\left(x^2+x-1\right)-x\left(x^3+x^2-3x-2\right)\)
\(\Leftrightarrow x^4+x^3-3x^2-2x+2-x^4-x^3+3x^2+2x\)
\(\Leftrightarrow2\)
\(\Leftrightarrowđ.p.c.m\)
(Thư lm thử thoy nha)
\(\left(x^2-2\right)\left(x^2+x-1\right)-x\left(x^3+x^2-3x-2\right)\)
\(=x^4+x^3-x^2-2x^2-2x+2-x^4-x^3+3x^2+2x\)
\(=0\)
Vậy biểu thức trên không phụ thuộc vào biến